26.5k views
5 votes
45 points help needed ASAP geometry

45 points help needed ASAP geometry-example-1

1 Answer

4 votes

Answer:

(3, 3 )

Explanation:

Under a translation < 2, 6 > , then

A(-5, - 3 ) → A'(- 5 + 2, - 3 + 6 ) → A'(- 3, 3 )

The line with equation x = 0 is the y- axis

Under a reflection in the y- axis

a point (x, y ) → (- x, y ), thus

A'(- 3, 3 ) → A''(3, 3 )

User Mohamed Farrag
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.